Penguatan Ruang Keagamaan Berbasis Resiliensi Sosial Masa Pandemi di Desa Patalan Ngawi - Jauhar, Moh. Irmawan; Bahroyni, Shodiqul; Mutawathi’i, Rolisa Wulan (Proceedings of Annual Conference on Community Engagement, 2022)
The team activities aim to strengthen religious spaces based on social resilience during the pandemic. The method used is ABCD with an emphasis on Asset Based Approach. In this case, the team did a mapping of the existing assets and made a schedule of activities aimed at strengthening the religious space. The results of the activity stated that the strengthening of social resilience-based religious space in Patalan with the initial step of mapping problems and assets as well as empowerment steps could not stand alone. In practice, the team received considerable assistance from community leaders, cultural and social values, as well as stakeholders who took an active role. Team also encouraged local religious leaders to become local resilience initiators so that their potential could find a channel. The activities carried out do not stop during the KKN period, but are followed by a follow-up program that aims to complement what was done during the KKN.